(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
By means of this modest study, we intend to present the great influence of dialecticism and regional words in the literary norm. The object of this paper is the finding of dialectal and regional words and the evidence of the weight and importance of the words, which enrich the lexicon of the Albanian language; the study of these words whether or not they have become part of the literary norm or whether they continue to be used or not in today’s spoken language. In the corpus of dialectal and regional words taken in the study, the most difficult and decisive issue was precisely the choice of words. Sometimes they are dialectal or grammatical phonetic variants and it looks like a new lexeme, with a new meaning. But another problem was also how to determine if they were already made part of the literary norm or not. This problem was analyzed in two main directions: a) in the synchronic, horizontal section and b) in the diachronic, vertical section. In synchronical cutting, the following main issues arise: 1) what was the basic principle of the selection of regional words and how did they become part of the literary norm. Neologisms created by Italian borrowings and authors will also be seen here. The discussion regards a written period, when a dictionary of the Albanian language had not yet been created and, moreover, we did not yet have a standard language. 2) which words from the spoken popular language are not reflected in the "Dictionary of the Albanian Language" In the diachronic section, a main issue emerges: what reflection has the literary lexicon collected found in the lexicon, has the evaluation criterion of the words changed, has the meaning changed, comparing them with the Dictionary of Albanian Language as well as other previous dictionaries FGJSSH 1980 [1] and FSHS [2] 2002? The methods used in this paper are diverse, such as: the method of analysis of theoretical sources: it was mainly used for determining the topic, collecting theoretical material, determining the bibliography, where a number of books by different authors were used such as: J. Thomaj "Lexicology of the Albanian language", R. Elsie History of Albanian literature etc. survey: the collection of dialect words by means of a questionnaire, which are the words that have not been accepted in the standard language and are still used in the spoken language. statistical method or meta-analysis for extracting the statistical results of the words in the study, with the help of the EXEL computer program. To reach the conclusions, we have used a wide literature, which includes both monographic studies and philological studies by different authors such as: R. Elsie, E. Çabej, J. Thomai, P. Haxhillazi, Xh. Lloshi, B. Dema, R. Memushaj, K. Kapinova, etc., while the collection of words was performed from the works of N. Mjeda, Gj. Fishta, E. Koliki, Migjeni.